The Role of Using Smartphones on Depression Rate in Retired Elderly - Nooshin Yoshany; Seyed-Saeed Ma; Hamideh Mihanpour; Somayeh-sadat; Sakineh Gerayllo; Asghar Nabil (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: Aging period is associated with potential threats such as loneliness and isolation. One of the most common mental disorders in the elderly is cognitive disorders and depression. Therefore, the purpose of this study was to investigate the role of smartphones use in depression in the retired elderly people of Yazd city. Materials and Methods: This cross-sectional study was conducted on 408 elderly people who were covered by the retirement center of Yazd province in 2018. The samples were selected through random sampling method. The questionnaires included demographic characteristics, internet usage, and GDS (Depression Scale). After data collection, analysis was performed using SPSS software version 18 and Mann-Whitney, Kruskal-Wallis and Chi-square. Results: 74.1% (74 people) of the elderly who used the Internet had  no depression and 38.4% (60 people) of the elderly reported the reason for using the mobile phone is obtaining information and severe depression in this group was less than the other group (8.3% including 5 people). Mean depression score by gender (p = 0.046), marital status, education, income, lifestyle (p≤0.001), and reason for internet use (p = 0.043) were significantly different in the two groups of Smartphone and non-Smartphone users. Conclusion: Given the results and the positive role of smart phones in reducing depression in the elderly, programs for the elderly need to be designed through social networks. Using the Internet and social networks can help increase the respect and confidence of older people at community level, and isolate and loneliness caused by child marriage, death of a partner, and physical and mental disabilities can be Reduced by using a Smartphone and improved the mental health of the elderly, also through proper policymaking and activation of support systems to improve their well-being, efforts can be made to achieve a favorable period for them.